Information, Self-Reference and Observation Theory in the Context of Social Sciences Epistemology - Juan Miguel Aguado (tripleC: Communication, Capitalism & Critique)
By attempting to fix an observable magnitude, the concept of information involves a cognitive model that enables a double ontological rupture: between subject and world, on one side, and between cognition and action, on the other side. A genealogical approach to information as a simultaneously epistemological and cognitive crossroad highlights the centrality of observation theory in the resolution of its contradictions. The recursive nature of observation inherent to informational logics makes constructivist assumptions especially relevant as a key contribution for an epistemological revision of the ideas of information and communication.